A case of a huge hemangioma involving the oro-maxillofacial region, pharynx, neck, and mediastinum - MAKINO, Shinya; HINOSHITA, Masahiro (Japanese Journal of Oral and Maxillofacial Surgery, 1998)
We report a case of a huge congenital hemangioma involving the oro-maxillofacial region, pharynx, neck, and mediastinum. A 28-year old man visited our clinic because of anorexia due to glossodynia and tongue swelling. He had a history hemangioma and had received irradiation, partial resection, and a skin graft between the ages of 1 to 5 years at other hospitals. The hemangioma extended from the head and neck to the mediastinum on initial examination. Angiographic and clinical findings suggested that this case was a purely venous malformation, and aggressive treatment was impossible. Nasal intubation under bronchofiberscopic guidance and needle cricothyrostomy for CO2 narcosis caused by the infected hemangioma were unsuccessful. The patient suffocated to death because of massive bleeding.